Antibiotic resistance profile and molecular characterization of extraintestinal pathogenic Escherichia coli (ExPEC) from human clinical samples in gaza strip, palestine. (14th December 2022) - Tayh, Ghassan; Elmanama, Abdelraouf; Selmi, Rachid; Slama, Karim Ben
Abstract: The rates of antibiotic resistance in extraintestinal pathogenic Escherichia coli (ExPEC) have increased significantly in recent years. This study aims at studying antibiotic resistance, virulence factors (VFs), and the phylogenetic background of ExPEC isolated from Palestinian patients. A total of 42 ExPEC isolates were collected from patients with extraintestinal infections in three Palestinian hospitals. Antimicrobial susceptibility was studied by the disk diffusion method. Resistance/virulence-gene profiles, phylogenetic groups, and integron profiles of these isolates were studied by PCR. The susceptibility to carbapenems was detected in 90.5% of the isolates. Half of the isolates were resistant to ampicillin and sulfamethoxazole/trimethoprim, and 33.3% of the isolates were multidrug-resistant. Bla TEM-1 was detected in seven isolates and bla OXA-1 was identified in one isolate. Sul, qnrA, and aac(6′)-Ib-cr genes were found in 12, 3, and 2 isolates, respectively. Class 1 integron has been identified in 10 isolates with the gene cassette arrangement dhfr17 + aadA5 . The isolates were distributed between phylogroups B2 and D. The presence of VFs, antibiotic resistance genes, and class 1 integron associated with phylogenetic groups (B2 and D) among multidrug-resistant (MDR)-ExPEC recovered from urinary tract infections (UTIs) patients will complicate infection management and increase therapy failure. Routine screening of antibiotic resistance is important for appropriate and efficient empirical treatment.